Being a solo librarian in healthcare : pivoting for 21st century healthcare information delivery - Burns, Elizabeth (Elizabeth Caire) (Chandos information professional series., 2015)
This title discusses current trends in healthcare librarianship, describes the daily job duties of a hospital librarian, looks at barriers to hospitals practicing evidence-based medicine, and connects improved patient care to healthcare librarian services.